Harnessing Ubiquitous Learning to Support Autistic Children's Educational Needs - , Jeyalakshmi Poornalingam (Archives of Current Research International, 2025)
Autism, often known as autism spectrum disorder (ASD), is a neurodevelopmental disorder, marked by limited interests, repetitive behaviours and difficulties with social interactions. While symptoms might be identified at various stages of lifespan, they usually manifest in early childhood. The severity of the disorder ranges from levels 1 to 3 depending upon the support the individual needs. Autistic children often experience difficulties with communication, social interaction and sensory processing, making traditional learning methods challenging. Ubiquitous learning provides flexible, individualized learning experiences that can be adapted to their unique needs, preferences and sensory sensitivities. The ability to learn in familiar, comfortable settings also minimizes social pressure, enabling children to focus more on acquiring new skills. As autism often involves difficulty in generalizing learned behaviors to new contexts, U-learning's mobile and adaptive nature supports the transfer of skills across various environments, fostering independence and confidence. The paper discusses the issues and possibilities of designing a syllabus, based on Ubiquitous learning, taking into consideration, their medical conditions. Autistic children have visual, auditory or tactile issues in handling gadgets and hence a unique syllabus is tailor made for each child taking care of their difficulties. The Wisconsin Scale, often used to assess developmental and behavioral traits in autism, can guide the creation of tailored syllabi that focus on enhancing communication, social skills and sensory processing for autistic children.